Yoga Therapy During Chemotherapy for Early-Stage and Locally Advanced Breast Cancer. (November 2022) - Greaney, Samantha K.; Amin, Neha; Prudner, Bethany C.; Compernolle, Maggie; Sandell, Linda J.; Tebb, Susan C.; Weilbaecher, Katherine N.; Abeln, Peri; Luo, Jingqin; Tao, Yu; Hirbe, Angela C.; Peterson, Lindsay L.
Background: Chemotherapy is associated with decreased quality of life (QOL), fatigue, depression, and weight gain in patients with breast cancer. Weight gain is associated with poorer prognosis. Yoga improves QOL, fatigue, and mood in women with breast cancer but its effect on treatment-related weight gain has not been studied. The aim of this trial was to determine the feasibility of personalized yoga therapy in women receiving treatment for early-stage or locally advanced breast cancer and assess its impact on weight gain. Methods: Thirty women were randomized 1:1 to receive yoga therapy by a certified yoga therapist during treatment or a control group. Participants in the yoga arm were asked to complete three 30 minute yoga sessions weekly (which included movement, breath work, mindfulness, and relaxation) throughout adjuvant or neoadjuvant chemotherapy (N = 29) or endocrine (N = 1); the control arm received breast cancer treatment without yoga. For comparability between participants randomized to yoga therapy, the single patient treated with endocrine therapy was excluded from the analysis. Primary outcomes were feasibility and weight change. Additional outcomes were mood, fatigue, QOL, serum tumor necrosis factor-alpha (TNF-alpha), and C-reactive protein (CRP) as immune mediator biomarkers. Results: Mean age was 51.6 years, 75.9% were white and 24.1% were people of color, reflecting the cancer center population. 80% had stage II-III disease. Enrollment was completed in 9 months. Compliance was lower than predicted; however, participants participated in on average 1.7 yoga sessions/week for a mean 15.6 weeks duration. There were no adverse events. Control arm participants gained on average 2.63% body weight during treatment while yoga participants lost 0.14% body weight (weight change = −0.36 in yoga arm vs. 2.89 in standard of care arm, Wilcoxon rank sum test P = .024). Control participants reported increased fatigue and decreased QOL, while yoga participants reported no change in QOL. No significant change in TNF-alpha or CRP was noted in either arm. Conclusion: This feasibility study suggests that personalized yoga therapy is beneficial for QOL and weight maintenance among women undergoing chemotherapy for early-stage or locally advanced breast cancer. Weight maintenance associated with yoga therapy may be of clinical significance in this population given the poorer prognosis associated with weight gain in breast cancer survivors. Trial Registration: NIH Clinicaltrials.gov #NCT03262831; August 25, 2017.https://clinicaltrials.gov/ct2/show/NCT03262831